The Cohesive Inter-relationship between the Semantic Layer of Language and the Literary Translations (With Reference to Few Literary Works Translated into Sinhala from English and Vice Versa) - Thilini Ferdinando, D. (University of Jaffna, 2014)
This research attempts to determine the cohesive inter-relationship between the semantic layer of language and literary translations with reference to the selected literary translations including prose, poetry and drama. This research also addresses the issues which arise when translating literary works without grasping the authentic meaning which the original author has conveyed through the original text. The paper tries to bring out the difficulties faced by the translator when successfully achieving the above challenge and also it reiterates that it is not an easy game of words using a dictionary. Subsequently the paper indirectly reinforces the idea that the linguistics knowledge is necessary for a translator especially the knowledge on semantic layer. The paper discusses salient points which are useful for a literary translator by drawing linkages to the semantic layer of the language supported by the selected literary works translated into Sinhala and vice versa and equivalents. The research uses the methodology of illustrating the meaning conveyed in the original text and analyzing the way in which it has been translated in the target text and measuring and weighing the effectiveness of translating the meaning by finding out the particular strategies used by the translator so as to convey the meaning effectively, comprehensively and vividly which enable the reader of the target language to enjoy and feel it in the very same way that the source language reader does.
Keywords: Equivalents; Literary Translation; Poetry; Prose; Drama; Semantic Layer